The world could end cervical cancer if it tried: an interview with Dr Shobha S Krishnan. (22nd August 2018) - Krishnan, Shobha S
Biography: Shobha S Krishnan is the Founder and President of the Global Initiative Against HPV and Cervical Cancer (GIAHC). She is a board-certified family physician and gynecologist and has been involved in the areas of primary care and women's health for over 30 years. She has extensive experience both nationally and internationally in the field of HPV and HPV-related diseases. Her vast experience in this field has given her a unique perspective on various issues related to HPV and its disease consequences. She is the author of the national and international award-winning book, The HPV Vaccine Controversy: Sex, Cancer, God and Politics (Praeger, 2008). Her book chapter on 'Challenges in Screening for Cervical Cancer' was recently published in Cancer Screening in the Developing World (University Press of New England, May, 2018). She is the chair of the HPV and Cervical Cancer Task Force at the American Medical Women's Association. She is also a member on the expert's panel of the American Sexual Health Association, Medical Advisory Board of the National Cervical Cancer Coalition and on the scientific committee at the Medical Women's International Association. In addition, she has served on the sexually transmitted disease research working group at Columbia University (NY, USA) and as a surveillance physician for the Centers for Disease Control. After completing her residency training, Krishnan went into private practice for 10 years before joining Columbia University, where she worked for several years. In December 2015, she received her master's certification in Non-Profit Leadership and Management from the University of Florida (FL, USA).